Clinical features and prognostic factors of Magnusiomyces (Saprochaete) infections in haematology. A multicentre study of SEIFEM/Fungiscope. Issue 1 (19th September 2022) - Del Principe, Maria Ilaria; Seidel, Danila; Criscuolo, Marianna; Dargenio, Michelina; Rácil, Zdenek; Piedimonte, Monica; Marchesi, Francesco; Nadali, Gianpaolo; Koehler, Philipp; Fracchiolla, Nicola; Cattaneo, Chiara; Klimko, Nikolai; et al.
Abstract: Background: Our multicentre study aims to identify baseline factors and provide guidance for therapeutic decisions regarding Magnusiomyces ‐associated infections, an emerging threat in patients with haematological malignancies. Methods: HM patients with proven ( Magnusiomyces capitatus ) M. capitatus or ( Magnusiomyces clavatus ) M. clavatus (formerly Saprochaete capitata and Saprochaete clavata ) infection diagnosed between January 2010 and December 2020 were recorded from the SEIFEM (Sorveglianza Epidemiologica Infezioni nelle Emopatie) group and FungiScope (Global Emerging Fungal Infection Registry). Cases of Magnusiomyces fungemia were compared with candidemia. Results: Among 90 Magnusiomyces cases (60 [66%] M. capitatus and 30 (34%) M. clavatus ), median age was 50 years (range 2–78), 46 patients (51%) were female and 67 (74%) had acute leukaemia. Thirty‐six (40%) of Magnusiomyces ‐associated infections occurred during antifungal prophylaxis, mainly with posaconazole ( n = 13, 36%) and echinocandins ( n = 12, 34%). Instead, the candidemia rarely occurred during prophylaxis ( p < .0001). First‐line antifungal therapy with azoles, alone or in combination, was associated with improved response compared to other antifungals ( p = .001). Overall day‐30 mortality rate was 43%. Factors associated with higher mortality rates were septic shock (HR 2.696, 95% CI 1.396–5.204, p = .003), corticosteroid treatment longer than 14 days (HR 2.245, 95% CI 1.151–4.376, p = .018) and lack of neutrophil recovery (HR 3.997, 95% CI 2.102–7.601, p < .001). The latter was independently associated with poor outcome (HR 2.495, 95% CI 1.192–5.222, p = .015). Conclusions: Magnusiomyces‐ associated infections are often breakthrough infections. Effective treatment regimens of these infections remain to be determined, but neutrophil recovery appears to play an important role in the favourable outcome.